(untitled) (International Journal of Physiotherapy, 2023)
Background: Yogic practices are beneficial for overall health and well-being, and they can potentially play a supportive role in the prevention and management of diabetes mellitus (DM) and reduce cardiovascular complications. While it is important to note that yoga should not be considered a standalone treatment for diabetes, it can be a complementary approach incorporated into a comprehensive treatment plan. This study assessed metabolic markers and wellness scores of post-menopausal diabetes patients to compare the benefits of yoga and therapy. Methods: The study recruited 15 female patients aged 36 to 63 who received medical treatment for type 2 DM at AIMSR. The patients were selected using an accidental sampling method. All participants provided informed consent to participate in the study. Among the recruited patients, 11 were post-menopausal for more than a year, and four were peri-menopausal. The study was designed pre- and post-intervention to assess changes in biochemical markers and subjective well-being. Results: The statistical analysis used the student’s t-test for paired samples. Using the paired t-test and accepting p-values less than 0.05 as statistically significant, the study aimed to determine if significant differences in the measured parameters existed before and after the intervention. The study findings suggest that yoga training resulted in decreased FBG significantly (P=0.0035) by 20.62%, PPBG also decreased significantly (P=0.0012) by 14.52%, and HDL increased significantly (P=0.022). There was a significant (P=0.003) decrease of 17.37% in the TC/HDL ratio and a significant (P=0.016) increase of 19.13% in the HDL/LDL ratio. Conclusion: In post-menopausal diabetes, a six-week yoga and physical therapy training program improves lipid profiles and blood sugar levels. Incorporating a comprehensive yoga and physical therapy treatment program into a successful complementary or integrative therapy program may improve the standard medical care for diabetes mellitus.